FACTORS AFFECTING THE DEVELOPMENT OF THE CREATIVE INDUSTRY IN KOTA PARI VILLAGE, SERDANG BEDAGAI REGENCY - Suwarno, Suwarno; Darmilisani, Darmilisani; Yosefa, Mira (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This research was conducted to determine and analyze the factors that influence the development of the creative industry. The research location is in Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency. The sample in this study is a community of business actors totaling 30 people. The analysis method used is multiple linear regression analysis and the calculation is assisted by the SPSS application version 25. The results showed that partially and simultaneously  the Workforce Owned (X 1 ), Technology Capabilities Owned (X 2 ), Easy Access to Communication (X 3 ), Creativity Owned (X 4 ) and Social Media (X 5 )  had  a positive and significant  effect on the Development of the Creative Industry (Y) with a percentage of influence of 54.3% .